Outro diálogo: uma compreensão do diálogo interno - Dias, Aline de Pinho (2009)
This thesis aims to enable a wider comprehension on thought operation as well as suggest alternatives for the formation of reflexive, critical, autonomous and creative individuals. The research defends the idea that it is possible for an individual to develop vigilant attention that makes thought flexibilization and change in the course of action, possible. This operation is called Internal Dialogue and is essentially characterized by a continuous openness towards novelty and learning. This makes it possible to minimize the usual way thought operates, in a automatic fashion (automatism). The research was based on theoretical references and ideas of David Bohm (1989;1994;2005) and Michael Polanyi (1983). The main emphasis was the understanding that a crisis situation enables awareness and state of alert that favors a more flexible thought pattern (Aragão Gomes, 1994, 1997). The methodology used was presentation and analysis of these moments through autobibliographical records with indication of crisis on behalf of the subjects. Other criteria were also used that enabled the composition of the analyzed material such as the fact that: the subjects were public and real, the data was available through accessible material; the subjects identified themselves as in crisis; these crisis were of varied kinds; they had different social, cultural and professional profiles. Thus, three auto-bibliographical elements were selected: the Infidel: the story of a woman that challenged Islam (2007), written by the political Muslim author Ayaan Hirsi; Still me: memories (2001), of the actor Christopher Reeve as well as Confessions of a Philosopher (2001), by the philosopher Bryan Magee. In these books an analysis was made related to parts that stated action an though operation that express internal dialogue. These were organized into categories that were pointed out as relevant for the identification of internal dialogue such as: Perceptions of physical reaction; emotions, beliefs and issues, individual actions, self judgment and thought, self questioning, comprehension, observation and empirical investigation, perception of the changes they performed in the world, escape of conditioning as well as action that resulted in new meaning. The analysis performed reinforces our goal once it sated that internal dialogue is an important tool that allows thought awareness, minimizing common automatism and making consciousness possible as well as favoring the occurrence of critical and reflexive thought. Thus, final considerations deal with the need for the development of teaching methodologies that address internal dialogue as a counterpoint to the many daily action that reinforce the automatism of thought